Desain dan Analisis Perubahan Fluks Magnet Terhadap Efek Peredaman Pada Prototipe Suspensi Pintar - Sadar Wahjudi (Polinema Press, Politeknik Negeri Malang, 2018)
The vehicle is one of basic needs for supporting mobility of people. Comfort and safety are demanded in every vehicle, especially in its suspension system. The existing suspension systems can’t maximize comfort and safety because it is still hydraulic and pneumatic based, without magnetic system. The purposes of the analysis is building magnetic suspension system with variations at the amount of coil and analyzing absorbing time. The methods of the analysis are determining concept, making the designs, determining components specification, making device block diagram, making wiring diagrams, making the device, taking the absorbing time datas, and the analyzing the data. The results of the analysis are the amount of coil is straight compared to the magnetic force and absorbing time. The most significant solenoid is the one which has 900 coils and has absorbing time at 9.6 seconds.